A record review study on the successfulness of radioiodine ablation in postoperative well differentiated thyroid carcinoma patients using 100 mci of 131i in HUSM - Ellyda, Muhammed Nordin (2009)
A record revtew study on the success of radioiodine ablation in postoperative well differentiated thyroid carcinoma patients using 100 mCi of 131i in HUSM. Well differentiated thyroid carcinoma is curable when discovered at an early stage. Postoperative radioiodine ablation is very useful. Its management. however. is often a challenge because there have been no prospective randomized trials and the optimal dose for successful single ablation is still a controversy. However. many published data showed a single high dose ablation is statistically significant in the treatment of post-operative well differentiated thyroid carcinoma. The objectives of this study are I) to detennine the prevalence of success of single dose of radioiodine ablation using I 00 mCi of 131 I. 2) to cotTelate successful ablation with other factors and 3) to determine the prevalence of patients that developed distant metastases after ablation therapy. This is a record review study over a period 10 years (1st January 1997 till 31st December 2007). A total of214 samples that fulfilled the inclusion criteria were studied. The attached formal reported result of first whole body scan and related associated factors were reviewed and the required data were retrieved and studied by the main researcher. The prevalence of successful ablation in our population was 54.2% which is slightly lower than that of reviewed published data from other countries. Total thyroidectomy was found to be the only significant associated factor in this study. The prevalence of patients developed metastases after initial ablation was 23.8% with lymph node being the commonest site of metastases. In this study, we conclude that the present ablative dose of 100 mCi is effective in the treatment of well differentiated thyroid carcinoma remnants. We also found that only the type of thyroid surgery had a significant association with the outcome of radioiodine ablation.